Economic Empowerment Strategies Through Entrepreneurship in Reducing Household Waste - Zubir Zubir; Ferdi Riansyah (FOUNDAE (Foundation of Advanced Education), 2025)
Household waste mismanagement remains a pressing issue in many regions, including Darul Imarah, Aceh Besar, Indonesia, leading to environmental degradation, health risks, and inefficient land use. Despite the persistence of poor waste management practices, community-driven entrepreneurial initiatives have emerged as an alternative pathway to strengthen the local economy and foster environmental awareness. This study aims to explore economic empowerment strategies through entrepreneurship to reduce household waste and promote community welfare. Employing a qualitative approach, data were collected via semi-structured interviews, focus group discussions, and document analysis involving 50 purposively selected participants, including entrepreneurs, community members, government officials, and environmental experts. Findings reveal that waste-based entrepreneurship has increased household income by 20–30%, generated over 100 jobs within two years, and reduced waste volume entering landfills by up to 35%. Compost production yielded the highest income growth (30%) and waste reduction (40%). Despite these benefits, challenges such as limited access to capital, inadequate infrastructure, and market barriers persist. This study contributes novelty by integrating the concepts of shared value and social business to show how local entrepreneurship can simultaneously drive economic and environmental outcomes. It also incorporates bibliometric mapping to visualize key thematic relationships in the field. In conclusion, a collaborative, policy-supported approach involving the government, private sector, and communities is crucial to sustaining waste-based entrepreneurship as a scalable model for green economic empowerment.